(untitled) (Journal of the College of Education for Women, 2019)
The study aimed to identify the social support and its relation with death anxiety forolds who are listed at the Palestinian ministry of social affairs in the Jerusalem governorate,the researcher uses the descriptive method and she bases her research on two types ofcriterion: the social support and the criterion of death anxiety, these two criterion are appliedon a stratified random sample, amounted to (184) of the elderly.The results show no statistical differences in the level of social support for olds whoare listed at the Palestinian ministry of social affairs according to the variables of sex.Whereas there are statistical differences in the level of social support for those olds accordingto the variable of the number of children for those who have more than seven children, inaddition to the variable of diseases they have comparing with those who do not suffer fromany disease. In addition, the data does not show statistical differences of death anxietyamongst the olds according to the variables of sex and the number of children. Nevertheless,these differences present in the death anxiety level according to the variable of age for thosewho are up to eighty years, the variable of diseases for those who have chronic diseases, thedata also shows that there is A relation between the death anxiety and the social support forthose olds who are listed at the Palestinian ministry of social affairs in the Jerusalemgovernorate.